Kolaborasi Pimpinan Pondok Pesantren dan Guru BK Dalam Mengatasi Kasus Bullying Di Kalangan Santri (Studi Pada Ponpes Perkampungan Minangkabau Padang) - Ahmad Putra; Nurfarida Deliani; Thaheransyah Thaheransyah; Bima Prasetya; Sri Kendiyol Jelisa (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This study discusses the efforts made by the leadership of the Minangkabau Islamic Boarding School and the guidance and counseling teachers in alleviating the problem of bullying that often occurs among students. This issue has become a serious polemic that cannot be ignored, so it needs to be resolved by taking several steps that have been attempted by the Leaders of the Islamic Boarding School. This type of research is field research or what is called qualitative research. The subjects in this study were the leaders of the Minangkabau Village Islamic Boarding School, BK teachers and several teachers as well as parties who were part of the Islamic Boarding School. The results of this study include the leadership making several efforts to overcome bullying cases, including: first, urging every teacher who teaches to evaluate the manners of the students in their daily lives, second, giving severe punishments for bullies, third, printing banners prohibiting bullying, fourth, monitoring the activities of students and the performance of the dormitory guardian during dorm hours, and fifth, discussions with counseling teachers in alleviating the problem of bullying.